Análise da variabilidade genética e de características agroindustriais em cana-de-açúcar - Duarte Filho, Luiz Sérgio Costa (2015)
Brazil is the largest producer of sugar and ethanol from sugarcane. The economic, social profile and the characterization of the sugarcane industry and its by-products are factors that distinguish this culture as one of the most important, both in agriculture and in industry. For the country to reach such importance in the sugarcane industry, the genetic improvement of sugarcane was key, especially by the increase in agroindustrial income, with gains of 1% to 2% per year. This work aimed to evaluate the results of a cultivar competition experiment with the main genotypes planted in Alagoas between 1975 and 2010, conducted between February 2012 and February 2013 in Plant Sinimbu, adopting the following statistical-genetic procedures: Mean estimates and grouping of cultivars to the main agroindustrial characteristics; Estimates of genetic parameters of the main agro-industrial characteristics, aimed at predicting future earnings; assessment of levels of genetic diversity of cultivars through molecular markers of the microsatellite type; recommendation of genetic crosses between cultivars in order to get future genetic gains in agro-industrial income. The experimental design of the trial was a randomized block with four replications. The plots consisted of three double rows of seven meters, spaced 1.50 mx 0.80 m, with an area of 48.3 m2. It was made sprinkler irrigation, applying four 30mm slides, one in the beginning of the experiment and the other at nine, ten and eleven months of age cane. The results obtained from the analysis of this study allow us to conclude that: the cultivars that showed the highest yields of sugar were RB92579, RB867515, RB99395 and RB951541; the higher heritability estimates and ratio of the genetic / environmental variance coefficients were for BRIX features, POL, TPH and TCH, indicating that most likely get future gains in the selection of superior individuals in these features, performing genetic crosses with genotypes this study; primers microsatellite SSR05, SSR06 and SSR93 were efficient in determining unique genetic profiles and discriminate relationship and genetic diversity of 21 cultivars evaluated in this study; and genetic crosses that can predict major gains in income in sugar are the cultivar RB92579 with RB867515 cultivars RB931003, RB931011, RB951541, RB98710 and RB99395.